2018
DOI: 10.5847/wjem.j.1920-8642.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Utility of point-of-care musculoskeletal ultrasound in the evaluation of emergency department musculoskeletal pathology

Abstract: Our study findings illustrate the utility of POCUS in the evaluation of a variety of musculoskeletal pathologies in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Ultrasonography is a powerful diagnostic method in musculoskeletal pathologies as it allows real-time, high-resolution examination [19]. The use of ultrasound in emergency services provides practical and reliable data [20]. The limits of the haematoma area were clearly demonstrated with the bedside ultrasound in our patient.…”
Section: Discussionmentioning
confidence: 68%
“…Ultrasonography is a powerful diagnostic method in musculoskeletal pathologies as it allows real-time, high-resolution examination [19]. The use of ultrasound in emergency services provides practical and reliable data [20]. The limits of the haematoma area were clearly demonstrated with the bedside ultrasound in our patient.…”
Section: Discussionmentioning
confidence: 68%
“…The use of POCUS has been documented to change management, prompting physicians to perform an arthrocentesis or abandon plans to perform the procedure based on sonographic findings and spare the patient from the procedure’s associated risks. 2 , 10 Given the demonstrated ability of POCUS to aid in arthrocentesis in prior literature, it seems reasonable to assume the potential benefit in training EM residents to utilize POCUS when evaluating for an effusion and performing an arthrocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that POCUS can aid in patient safety as a tool for procedural needle guidance. 2 , 16 Ultrasound needle guidance was found to reduce the number of attempts and decreased patient-reported pain compared to landmark technique and maximizing the amount of fluid removed during an arthrocentesis. Given this support from the prior literature, adequate needle visualization was a key component of the arthrocentesis didactic session the residents received.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ultrasound to delineate the structures of the musculoskeletal system is well-documented throughout the literature [22]. Point-of-care ultrasound has been shown throughout the literature to be a useful tool when diagnosing various musculoskeletal pathology, identifying structures and aiding various musculoskeletal procedures [23].…”
Section: Discussionmentioning
confidence: 99%